2015
DOI: 10.1155/2015/489647
|View full text |Cite
|
Sign up to set email alerts
|

miR-103 Regulates Oxidative Stress by Targeting the BCL2/Adenovirus E1B 19 kDa Interacting Protein 3 in HUVECs

Abstract: Oxidative stress plays a critical role in cardiovascular diseases. Salidroside, a glycoside from Rhodiola rosea, has been used as an antioxidative therapy for oxidative injury in cardiac diseases. However, the mechanism underlying its antioxidant effect needs to be elucidated. Treatment of HUVECs with H2O2 significantly decreased the expression of miR-103 in a dose- and time-dependent manner, whereas pretreatment with salidroside significantly inhibited this decrease. Subsequent analysis showed that overexpres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 33 publications
2
23
0
Order By: Relevance
“…In vitro oxidative stress response was stimulated by cell treatment with H 2 O 2 . In accordance with previous studies, the degree of H 2 O 2 -induced cell damage was time-and concentrationdependent [19]. The damage induced by 1 mM H 2 O 2 in cells treated for different times was evaluated with an MTS kit ( Figure 1(a), * P < 0:05, * * P < 0:01).…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…In vitro oxidative stress response was stimulated by cell treatment with H 2 O 2 . In accordance with previous studies, the degree of H 2 O 2 -induced cell damage was time-and concentrationdependent [19]. The damage induced by 1 mM H 2 O 2 in cells treated for different times was evaluated with an MTS kit ( Figure 1(a), * P < 0:05, * * P < 0:01).…”
Section: Resultssupporting
confidence: 84%
“…MicroRNAs, composed of 20-40 nucleotides, are highly conserved single-stranded noncoding RNA, that regulate gene expression in many biological processes [17,18]. The gene coding region for miR-103 is located on human chromosome 5 and belongs to the miR-103/107 gene family [19], which is widely expressed in various tissues. In fact, several studies have shown that inhibiting the expression of miR-103 may result in a protective effect in cardiovascular diseases.…”
Section: Introductionmentioning
confidence: 99%
“…The tumour suppressor miRNAs, such as miR‐145 and miR‐103, commonly target Bnip3. However, oxidative stress induced by H 2 O 2 reduces expression of miR‐145 and miR‐103 in neonatal rat ventricle myocytes and HUVECs, which consequently leads to Bnip3 pathway induced cell death in those cells . On the other hand, H 2 O 2 induced elevation of miR‐150 and miR‐181a promote oxidative stress induced apoptosis by inhibiting c‐myb and GPx1, respectively .…”
Section: Mirnas Regulate Mitochondrial Reactive Oxygen Species (Ros) mentioning
confidence: 99%
“…It has been shown that many of the miRNA families play important roles in oxidative stress, and different miRNAs have contrary functions [16-18, 39, 40]. For example, overexpression of miR-103 significantly reduced oxidative stress induced by H 2 O 2 by targeting the BCL2/Adenovirus E1B 19 kDa interacting protein 3 [16]. Gao et al demonstrates that miR-214 protects erythroid cells against oxidative stress by ATF4 and EZH2 [39].…”
Section: Overexpression Of Ampkα1 Is Essential For Protective Effect mentioning
confidence: 99%
“…Increasing evidence indicated that miRNAs are involved in oxidative stress [13]. Lots of miRNAs have been identified to have protective effect or damage effect, which is dependent on the role of their target genes, including miR-424 [14], miR-25 [15], miR-103 [16], miR-144 [17] and miR-122 [18]. These outcomes show a strong basis for the importance of miRNAs in the pathogenesis of CVD.…”
Section: Introductionmentioning
confidence: 99%